Electrophoretic deposited LSCF-SDCC-Ag cathode coating on ferritic stainless steel interconnect for SOFC - Omar, Noor Irinah; Kang, Huai Tan; Taib, H.; Abd. Rahman, Hamimah (IOP Publishing, 2018)
The application of electrophoretic deposition (EPD) technique in development of composite cathode as a coating layer on ferritic stainless steel (FSS) interconnect for solid oxide fuel cell (SOFC) has acquired a great interest. The aim of this study is to determine the capability of EPD technique in producing composite cathode coating. The lanthanum strontium cobalt ferrite (LSCF)-samarium doped ceria carbonate (SDCC) composite cathode powder with silver (Ag) addition was fabricated adopting the EPD technique. LSCF-SDCC-Ag suspension was prepared by using organic-aqueous solvent for the deposition. The coated FSS substrate was first heat treated at 600°C for 90 minutes in air. The deposition was carried out at different applied voltages (5, 7 and 10 volt) and deposition durations (5-20 minutes). The increment of applied voltage and deposition duration was found to contribute to the increment of LSCF-SDCC-Ag deposited weight. The highest deposited weight and thickness of coating was 2.47 mg/cm² and 62.73 µm respectively attained by deposition of 10 volt for 20 minutes. According to the obtained results, deposition at 10 volt within 5 to 20 minutes has shown a better deposition. It is thus clear that EPD is indeed a feasible technique applicable for the development of composite cathode for SOFC interconnects and yielded better coating thicknesses of LSCF-SDCC-Ag on FSS interconnect for SOFC.